Terrestrial Broadcast Transmission of Digital HDTV Signals - 姚庆栋; 仇佩亮; 王匡 (Tongxin xuebao)
With a brief discussion of the fundamental requirement of FCC（U.S.A）on the terrestrial broadcast transmission of digitized HDTV,propertties and techniques of some proposals of U. S.A and Europe are summarized in this paper,the features of terrestrial broadcast channel is also discribed.In this paper the emphasis is placed on the discussion of GA scheme and COFDM for HDTV transmission. Some recent research trends on HDTV transmission are briefly described in this paper.